1961
DOI: 10.1111/j.1476-5381.1961.tb00309.x
|View full text |Cite
|
Sign up to set email alerts
|

Some Inhibitors of Histamine‐induced and Formaldehyde‐induced Inflammation in Mice

Abstract: The swelling and capillary hyperpermeability of the mouse foot in response to an injection of formaldehyde, and the increased capillary permeability to an intradermal injection of histamine, have been investigated. Cortisone, mepyramine and sodium salicylate were effective in reducing histamine-induced inflammation, sodium salicylate being less active in the adrenalectomized animal. In formaldehyde-induced inflammation, however, cortisone was ineffective whereas sodium salicylate was effective in the intact mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

1962
1962
1975
1975

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 14 publications
1
12
1
Order By: Relevance
“…It is well known that the salicylates, for example, release both adrenal cortical (Smith, 1953) and adrenal medullary hormones (Smith, 1955), and although the adrenal cortical hormones are inactive against formaldehyde-induced inflammation in the mouse foot (Northover & Subramanian, 1961a) the adrenal medullary amines have been shown in the present experiments to be active.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…It is well known that the salicylates, for example, release both adrenal cortical (Smith, 1953) and adrenal medullary hormones (Smith, 1955), and although the adrenal cortical hormones are inactive against formaldehyde-induced inflammation in the mouse foot (Northover & Subramanian, 1961a) the adrenal medullary amines have been shown in the present experiments to be active.…”
Section: Discussionsupporting
confidence: 51%
“…Numerous reports have been published on the anti-inflammatory action of salicylates, and the subject was reviewed by Smith (1953) and Smith (1960). Previously we have found (Northover & Subramanian, 1961a) that formaldehyde-induced inflammation in the mouse foot is reduced by both acetylsalicylic acid and sodium salicylate, and it seemed of interest to investigate the effect of other hydroxybenzoates. The results of these experiments are given in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hinshaw, Brake, Emerson, Jordan & Masucci (1964) reported that adrenalectomized dogs were more sensitive to endotoxin, which suggested that catecholamines play a protective role. Adrenaline and noradrenaline have been reported to suppress inflammation (Setnikar, Subratorra & Temilcou, 1959;Northover & Subramanian, 1961). These studies on the release of chemical mediators by endotoxin were carried out after its intravenous administration.…”
Section: Discussionmentioning
confidence: 99%